THE IMPLICATIONS OF CONSTITUTIONAL COURT DECISION REGARDING THE LIMITATION OF REGIONAL HEADS' TERMS ON THE CONSTITUTIONALITY OF REGIONAL HEADS' NOMINATIONS - Noor, Andreyan; Yulianingrum, Aullia Vivi; Elviandri, Elviandri; Alhadi, Muhammad Nurcholis (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
The limitation of regional heads' terms in Indonesia is basically related to two things, the first is to avoid abuse of authority, and the second is to regenerate leadership in the regions, therefore the limitation of the regional heads' terms is very important. This research is normative legal research with a statute approach and a case approach, by analyzing the decisions of the Constitutional Court such as Decision Number 22/PUU-VII/2009, Number 67/PUU-XVIII/2020, and Number 2/PUU-XXI/2023. This study examines how the Constitutional Court interprets the term limits of regional heads, including the calculation of the term of office for regional heads who do not complete their term of office. The results of this study show that the Constitutional Court emphasizes that a term of office that is served for half of the term or more is counted as one full term, both for definitive officials and temporary officials. This interpretation aims to ensure legal certainty and prevent abuse of power, by providing protection for the constitutional rights of citizens who wish to run for re-election. The Constitutional Court's decision also confirms that the norm of term limits for regional heads is in line with the principles of justice, proportionality, and legal certainty guaranteed in the 1945 Constitution. Thus, this term limit is not only served to prevent the dominance of power, but also to encourage the regeneration of healthy leadership in the Indonesian democratic system. The implications of this Constitutional Court decision are very important for the implementation of the 2024 Simultaneous Regional Head Elections, where the KPU and Bawaslu must ensure the consistent implementation of this norm, to ensure the creation of fair, transparent, and quality elections.